Risk Mitigation of Toll Road Development (Case Study of Trans Sumatera Toll Road) - Mandia, I Wayan; Wahyuni, Putu Ika; Sinarta, I Nengah (Fakultas Teknik Universitas Brawijaya, 2022)
To achieve the level of infrastructure performance as a middle-income country by 2025, as well as to catch up with the backwardness of infrastructure, specifically for toll road projects, the government targets that by 2021 Indonesia will have 5200 km of toll roads. Hence, there is a significant increase of 3000 km. The government, especially in the development of toll road infrastructure, gives a more significant portion to the purely private sector, BUMN, and Public Private Partnership - Government Business Entity Cooperation. Risk analysis is carried out by structuring risk using the RBS (Risk Breakdown Structure) method and multiplying the impact value and frequency to get the risk level value for each risk factor. The results of the analysis obtained from RBS are further analyzed based on the practical experience of project implementers to determine their actions in overcoming risks, then analyzed and discussed again using a table comparing the amount of risk, comparison of the level of importance of risk (importance level) and the level of risk based on the payment system. The results obtained from this study are the types of risk and the level of risk at each stage of the project.